Uric Acid, the End-Product of Purine Metabolism, Mitigates Tau-Related Abnormalities: Comparison with DOT, a Non-Antibiotic Oxytetracycline Derivative - Bianca Andretto de Mattos; Rodrigo Hernán Tomas-Grau; Thaís Antonia Alves Fernandes; Florencia González-Lizárraga; Aurore Tourville; Ismaila Ciss; Jean-Michel Brunel; Rosana Chehin; Annie Lannuzel; Laurent Ferrié; Rita Raisman-Vozari; Bruno Figadère; et al. (Biomolecules, 2025)
We aimed to simulate tau abnormalities—specifically hyperphosphorylation and aggregation—that are hallmarks of tauopathies, including Alzheimer’s disease, to evaluate tau-targeting therapies. To model pathological p-tau accumulation at early disease stages, we exposed mouse cortical cultures to redox-active iron from hemin (Hm), a breakdown product of hemoglobin, or challenged them with the excitatory neurotransmitter glutamate. Using the AT8 phospho-specific antibody, we demonstrate that a subtoxic concentration of Hm (3 µM) promotes pathological p-tau accumulation in a subpopulation of cultured cortical neurons and their proximal neurites. Uric acid (UA; 0.1–200 µM), the metabolic end-product of purines in humans, prevented p-tau build-up. Neither xanthine, the immediate precursor of UA, nor allantoin, its oxidized product, reproduced this effect. Live cell imaging studies revealed that UA operates by repressing iron-driven lipid peroxidation. DOT (3 µM), a brain-permeant tetracycline (TC) without antibiotic activity, mimicked UA’s anti-tau and antioxidant effects. Interestingly, both UA and DOT remained effective in preventing p-tau accumulation induced by glutamate (10 µM). To simulate tau aggregation at more advanced disease stages, we conducted a Thioflavin-T aggregation assay. Our findings revealed that UA and DOT prevented tau aggregation seeded by heparin. However, only DOT remained effective when heparin-assembled tau fibrils were used as the seeding material. In summary, our results indicate that UA-elevating agents may hold therapeutic utility for tauopathies. The non-purine compound DOT could serve as an effective alternative to UA-related therapies.